Chlorinated hydrocarbons in infertile women - Gerhard, Ingrid; Monga, Bondo; Krähe, Joachim Harald; Runnebaum, Benno (Environmental research, 1999)
This study was conducted to investigate the hypothesis that chlorinated hydrocarbons (CHC) may affect fertility in women. In 489 infertile women, CHC levels were measured in whole blood. Different anamnestic and clinical parameters were obtained or investigated in order to detect possible associations to CHC concentrations. CHC levels were correlated to the women's age, body mass index, and nationality. Especially in women with uterine fibroids, endometriosis, miscarriages, persistent infertility, and hormonal disturbances, elevated concentrations of chlorinated hydrocarbons with long half-lives were observed. Chlorinated hydrocarbons may play a role in female infertility and may be an underlying factor in certain gynecological conditions.
Available online 25 May 2002
Gesehen am 18.11.2020